A low‐radar cross section Vivaldi antenna array based on reflection cancelation. Issue 3 (10th December 2021) - Zhao, Chumeng; Jiang, Wen; Ge, Jiangcheng; Xi, Yan; Hong, Tao; Gong, Shuxi
Abstract: In this article, a low radar cross section (RCS) Vivaldi antenna array based on reflection cancelation is proposed, which is composed of two antenna elements. By using different feed structures and loading metal strips of different lengths, the two antenna elements have approximately 180° reflection phase difference from 5.1 to 11.9 GHz under y ‐polarized incident waves and good impedance matching performances from 8 to 12 GHz. Then the different antenna elements are fed by power dividers to form different subarrays. Furthermore, shape modification is applied to the array, which is composed of different subarrays. Finally, RCS reduction of proposed array is achieved in 5.2–12 GHz under y ‐polarized incident waves compared with reference array, with a maximum reduction value of 16 dB. At the same time, the proposed array has good radiation characteristics. The prototype of proposed array is fabricated and measured to verify the design. The simulated results and measured results are in good agreement.